2009
DOI: 10.1080/07481180903142407
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality, Problem-Solving Skills, Attachment Style, and Hopelessness in Turkish Students

Abstract: Among 180 Turkish university students, the probability of suicide was strongly predicted by both hopelessness and deficiencies in problem solving. In addition, for women, unhealthy attachment styles (preoccupied and dismissing) also predicted suicidality. The clinical implications of these findings are that psychotherapists should focus on helping suicidal adolescents improve their problem solving skills and decreasing their hopelessness and, for women, assisting them to develop healthier relationship styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 19 publications
1
29
1
3
Order By: Relevance
“…Previous studies have shown that the suicide rate in Islamic populations is considerably lower than in Western countries (Colucci et al 2008;Lester 2006). This is explained by the fact that the religion Islam severely prohibits suicide (Zeyrek, Gençöz et al 2009). Additional explanation for the low reporting rate of suicidal behavior in Islamic populations is that individuals who plan to commit suicide know that they will almost certainly be blamed by other people and that if they survive, they will suffer greatly from their own stigma at having attempted suicide.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that the suicide rate in Islamic populations is considerably lower than in Western countries (Colucci et al 2008;Lester 2006). This is explained by the fact that the religion Islam severely prohibits suicide (Zeyrek, Gençöz et al 2009). Additional explanation for the low reporting rate of suicidal behavior in Islamic populations is that individuals who plan to commit suicide know that they will almost certainly be blamed by other people and that if they survive, they will suffer greatly from their own stigma at having attempted suicide.…”
Section: Introductionmentioning
confidence: 97%
“…Insecure attachment is associated with suicidal ideation and attempt in mostly cross-sectional studies of adolescent samples. 213 Our and others' studies found that insecure attachment in adults was associated with their suicide attempt history, 14 suicidal ideation, 15 and risk of suicide attempt during one-year, prospective follow-up. 16 …”
Section: Introductionmentioning
confidence: 66%
“…al., 2011;Adam, Lohrenz, Harper, & Streiner, 1982). When the previous studies in the literature are analyzed, it is seen that individuals who have suicidal behavior have mainly avoidant attachment styles (Blatt &Homann, 1992;Zeyrek et. al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In studies on alignment of suicide attempts and styles, an insecure attachment style is thought as responsible risk factor (Grunebaum et. al., 2010;Mandal & Zalewska, 2011;Zeyrek, Gençöz, Bergman, & Lester 2009). Studies evaluating the relation between attachment and suicide have mainly been carried out with children and adolescents (Baca-Garcia et.…”
Section: Introductionmentioning
confidence: 99%